Perancangan Arsitektur Enterprise Menggunakan Kerangka Kerja TOGAF ADM Pada Hotel MALEO Ambon - Yong Giovani Edbert; Johan Tambotoh (STMIK Banjarbaru, 2023)
The use of information systems that have not been optimal in supporting business processes at the hotel so that it is necessary to improve and optimize the system that has been used at Maleo Hotel in order to improve hotel services and business processes, this study aims to design enterprise architecture by identifying GAPs to develop systems and add systems that are needed, and integrate systems so as to produce a well-integrated system. The method used in this research is TOGAF Framework, as a tool for enterprise architecture design in the Preliminary phase, Business Architecture, Application Architecture, Information System Architecture, Technology Architecture, Opportunites & solutions and Migration Planning owned by TOGAF ADM to produce Information System design and technology in improving service and service management performance and increasing the efficiency of business activities of Maleo Ambon Hotel.Keywords: TOGAF ADM; information systems; architecture enterprise; Hotel AbstrakPenggunaan sistem informasi yang belum optimal dalam mendukung proses bisnis pada hotel sehingga dibutuhkannya peningkatan dan pengoptimalan sistem yang telah digunakan pada Hotel Maleo agar dapat meningkatkan pelayanan dan proses bisnis hotel, Penelitian ini bertujuan merancang arsitektur enterprise dengan cara mengidentifikasi GAP untuk mengemabangkan sistem dan menambah sistem yang diperlukan, serta mengintergrasi sistem sehingga dapat menghasilkan sistem yang terintergrasi dengan baik. Metode yang digunakan dalam penelitian ini menggunakan Kerangka Kerja TOGAF, sebagai alat bantu perancanagan arsitektur enterprise pada fase Preliminary, Business Architecture, Application Architecture, Information System Architecture, Technology Architecture, Opportunites & solutions dan Migration Planing yang dimiliki TOGAF ADM untuk menghasilkan perancangan Sistem Informasi dan teknologi dalam meningkatkan pelayanan dan kinerja manajemen pelayanan dan meningkatkan efisiensi aktivitas bisnis Hotel Maleo Ambon.